Biological material spider silk by direct incorporation onto fiber ferrule for wavelength tunable Q-switched application - Muhammad, N A M; Awang, N A; Basri, H; Zalkepali, N U H H; Supaat, M I (iop, 2024)
This study presents a novel structure saturable absorber (SSA) based on spider silk for wavelength tunable Q-switched erbium-doped fiber laser (EDFL) operation from S to L bands. The nonlinear optical absorption of spider silk was measured, showing a high modulation depth of 64.92%, a low saturation intensity of 0.03 MW cm−2 , and a non-saturable loss of 24%. By adjusting the polarization controller, a wavelength tunable Q-switched EDFL was achieved, with a tuning range of 64 nm from 1522 nm to 1586 nm. The Q-switched pulses had a repetition rate varying from 20.62 kHz to 6.57 kHz and a pulse width ranging from 14.02 µs to 26.30 µs, corresponding to an output power from −11.31 dBm to −9.02 dBm at the maximum pump power of 151.40 mW. The proposed SSA using spider silk offers a low-cost, eco-friendly, and high-performance solution for wide wavelength tunable Q-switched EDFL applications in optical testing, fiber communication, optical fiber sensing, and ultrafast lasers.